Empowering Future Leaders: The Role of Religious Institutions in Addressing Social Issues Through Training and Community Engagement - Purwanto, Edi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2024)
Religious institutions are pivotal in addressing social issues, acting as agents of spiritual guidance and societal transformation. This study examines a community service program at Victory Theological College, designed to prepare future religious leaders through an integrated approach to theological education and practical social engagement. The program encompassed three phases: interactive training on social justice and contemporary issues, hands-on field practice addressing real-world challenges, and reflective evaluations to assess impact and learning. Participants demonstrated significant improvement in understanding the dual role of religious institutions in providing social aid and advocating for justice. Field activities included initiatives to combat poverty, promote racial reconciliation, foster gender equality, advocate for environmental stewardship, and support human rights. Reflective discussions highlighted the program’s success in connecting theological principles with practical solutions, preparing leaders to navigate complex social realities. The study underscores the transformative potential of combining faith-based education with community engagement, offering a replicable model for fostering justice, compassion, and sustainable development through religious institutions.